Guarantee of Legal Assurance and Justice for the Implementation of Consumer Financing - Dhaniswara K. Harjono; Aarce Tehupeiory; Heddy Kandou (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2022)
This study aims to determine how to guarantee legal certainty and justice for the implementation of consumer financing. This study was conducted at the Christian University of Indonesia in 2021 for four months, starting from March – June 2021. The research method used was normative legal research, focusing mainly on fiduciary guarantee legislation and the theory of legislation, justice, and legal certainty. The findings of this study are that if the debtor/consumer of consumer financing is in default, based on Constitutional Court Number 18/PUU-XVII / 2019, creditors of consumer finance companies cannot carry out direct execution of the object of collateral. It must refer to the provisions of Article 15 paragraph (2) of the UUJF, namely through fiat execution as the implementation of court decisions that have permanent legal force.